Evaluation of impact teeth prevalence and related pathologic lesions in patients in Northern part of Iran (2014-2016) - Pakravan, Amir Hosein; Nabizadeh, Mohammad Mehdi; Nafarzadeh, Shima; Jafari, Sina; Shiva, Atena; Bamdadian, Tahmineh (Journal of Contemporary Medical Sciences, 2018)
Objective: In this research, our purpose was to evaluate how prevalent impacted tooth is. We also evaluated the type of third molar impaction and pathologic lesions related to impacted teeth in patients reffered to Sari and Babol dental school in 2014-2016. Methods: The study was cross-sectional, and was carried out on 2109 panoramic radiographs of patients with age over 20 years referring to Sari and Babol dental faculties during 2014-2016. Results: Among the patients, 392 (18.5%) presented with at least one impacted tooth. 243 women (20.6%) and 149 men (16%) had impacted teeth. Conclusion: The most common encountered impact tooth was found to be the third molar of mandible and dentigerous cyst was the most detected lesion associated with tooth impaction.